Development of a Multiplex TaqMan Assay for Rapid Detection of Groundnut Bud Necrosis Virus: A Quarantine Pathogen in the USA - Anushi Suwaneththiya Deraniyagala; Avijit Roy; Shyam Tallury; Hari Kishan Sudini; Albert K. Culbreath; Sudeep Bag (Viruses)
Groundnut bud necrosis orthotospovirus (GBNV), a tripartite single-stranded RNA virus, poses a significant threat to United States agriculture. GBNV is a quarantine pathogen, and its introduction could lead to severe damage to economically important crops, such as groundnuts, tomatoes, potatoes, peas, and soybeans. For the rapid and accurate detection of GBNV at points of entry, TaqMan reverse transcriptase–quantitative polymerase chain reaction (RT-qPCR) assays were developed and the results validated using conventional reverse transcriptase–polymerase chain reaction (RT-PCR) followed by Sanger sequencing. These assays target highly conserved regions of the nucleocapsid (NP) and movement (MP) proteins within the viral genome. Multiplex GBNV detection assays targeting the NP and MP genes, as well as an internal control plant gene, ACT11, showed efficiency rates between 90% and 100% and R2 values of 0.98 to 0.99, indicating high accuracy and precision. Moreover, there was no significant difference in sensitivity between multiplex and singleplex assays, ensuring reliable detection across various plant tissues. This rapid, sensitive, and specific diagnostic assay will provide a valuable tool at ports of entry to prevent the entry of GBNV into the United States.